Implementasi Teaching at the Right Level (Tarl) Terhadap Pencapaian Profil Pelajar Pancasila pada Mata Pelajaran Pendidikan Pancasila Siswa Kelas 5 Sekolah Dasar - Ainun Hania; Kartinah Kartinah (Mathematics Education Study Program, 2025)
This study aims to examine the implementation of the Teaching at the Right Level (TaRL) approach in achieving the Pancasila Student Profile dimensions of critical thinking and collaboration in the Pancasila Education subject for fifth-grade elementary school students. The research employs a mixed methods design, combining Descriptive Qualitative and Quasi-Experimental Research methodologies. Data collection techniques include interviews, observations, and pre-test and post-test worksheets. The research subjects comprise 48 elementary school students, divided into Class 5A as the experimental group and Class 5C as the control group. This study's results show that using the Teaching at the Right Level (TaRL) approach enables students to achieve the Pancasila Student Profile dimensions of collaboration and critical thinking. Based on classroom observations and interviews, students demonstrated increased activity in helping their peers, sharing ideas, and working together to complete group tasks. Furthermore, the independent sample t-test results indicate a significant value of 0.00 in the post-test, which is lower than 0.05. This finding demonstrates that the Teaching at the Right Level (TaRL) approach effectively helps fifth-grade students of SDN Karanganyar Gunung 02 achieve the Pancasila Student Profile dimensions of critical thinking and collaboration in the Pancasila Education subject